Artificial intelligence as a legal category and object of legal regulation - Sidorova, N.V.; Dulatbekov, N.O.; Kusainova, L.K. (Bulletin of the Karaganda University “Law Series”, 2024)
The purpose of this study is to analyze «artificial intelligence» as a legal category and object of legal regulation, in the context of discussing the directions of introduction of artificial intelligence in legal processes, as well as in the activities of the judiciary and law enforcement agencies. Improvement of digital processes of accessibility of justice to the population of the Republic of Kazakhstan is a reality of today, but one of the factors hindering these trends is the lack of legal support for the integration of artificial intelligence in digital processes. The introduction of artificial intelligence into the digital platform of critical objects of information and communication infrastructure requires legal regulation. These aspects determine the relevance of the present study. The methodological basis of the work includes the analysis of «artificial intelligence» at the theoretical level by combining traditional methods of induction and deduction, axiomatic method, analysis and synthesis of doctrinal provisions, legal norms (domestic and foreign in a comparative aspect), as well as law enforcement practice. A significant part of the study is devoted to the analysis of the normative legal framework that determines the legal prerequisites for the integration of artificial intelligence into the digital space of critical objects, including judicial and law enforcement activities. The study found that «artificial intelligence » as a legal category has not been developed not only at the legislative level, but also insufficiently researched in theory. Legal regulation of artificial intelligence is minimized, despite the introduction of artificial intelligence tools in legal processes. The results of the conducted research are the authors’ formulation of the legal category «artificial intelligence», substantiation of the directions of legal regulation of artificial intelligence as a significant tool of digitalization and informatization. The main result substantiated by the authors is the formation of a frame of legal norms on artificial intelligence in the process of codification of legislation in the field of digitalization.